Production of environmentally friendly, sustainable insulation material: Fly ash-based geopolymer - Arioz, Evren (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Geopolymer foams are sustainable, environmentally friendly, and low-cost materials. In this research, fly ash-based geopolymer foams were synthesized using a mixture of sodium hydroxide, sodium silicate, and hydrogen peroxide as the foaming agent. At a constant 80◦C curing temperature, curing periods were varied to 4, 15, and 24 hours, while hydrogen peroxide ratios were varied to 0.5%, 1%, 1.5%, and 2%. The effects of peroxide amount and curing duration on thermal conductivity, density, compressive strength, and microstructural properties were examined. The densities and thermal conductivity values decreased with increasing curing duration and hydrogen peroxide ratio. The lowest density was recorded as 1070 kg/m3 for the sample prepared with 2% hydrogen peroxide and cured for 24 hours. Conductivity values varied from 0.247 to 0.108 W/m K. The highest compressive strength value obtained was 9.3 MPa. Quartz and mullite were identified as crystalline phases. The hydrogen peroxide content did not significantly affect the crystalline structures. The weight loss decreased as the hydrogen peroxide ratio increased, according to TGA analysis. BET analysis indicated that the pore size distribution shifted to the smaller pore size region as the peroxide concentration increased. SEM analyses showed a reduction in the presence of unreacted fly ash residues in the samples containing 1.5% and 2% hydrogen peroxide. The geopolymer foams produced in this experimental study meet RILEM requirements for structural and insulating concrete materials with respect to thermal conductivity and compressive strength.